Growth and reproductive biology aspects of sea urchin population of Lytechinus variegatus Lamarck, 1816 (Echinodermata: Echinoidea) from the Ribeira Beach, Salvador, Bahia, Brazil - Lopes, Cecília da Paixão; Cerqueira, Walter Ramos Pinto (SITIENTIBUS série Ciências Biológicas, 2007)
This document intends to know growth aspects and reproductivebiology of a sea urchin population of the Lytechinus variegates species from the infralitoral of Ribeira Beach, located at Todos os Santos Bay, in Salvador city, BA, between April and September, 2006. The studied material was collected monthly, in low-tides and, at each one of them, were established five sampling points, counted from a tracing with a profile of fifty meters, perpendicular to the beach line, where at every ten meters from the profile, were looked for, ad libitum, ten specimens, whose carapaces height and diameter were measured in situ, by a paquimeter, totalizing fifty unites. Monthly, twenty specimens were collected ad libitum, anesthesied, fixed and taken to the laboratory, where they were also measured (carapace height and diameter), weighted (total humid weight), dissected, and had their Gonads and Aristotle’s lantern removed and weighted. Morphometric aspects were analyzed, like the carapace height and diameter, gonadal index, and Aristotle’s lantern index. The data obtained was put inMicrosoft Excel® spread sheets, and statistically analyzed. Significant variations were not perceived among diameter, height and weight middle values of the specimens along the months. Significant correlations among variants were perceived only between width and height and between gonadal index and Aristotle’s lantern index. The best variant to estimate the Lytechinus variegatus growth was the carapace diameter. The weight varies a lot among specimens in each population and the variety is related by plenty of body parts. In the studied area, the spawning period is between July and September.